Jedność i podział władzy - Ławniczak, Artur (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The book is dedicated to one of main problems in the area of political law, that is the issue of doctrinal unity or, alternatively, disunity of power. We can see this problem in the Carl Schmitt’s concept of the secondary nature of state law in relation to theological and canonical findings. We conclude that we must first look at the problem of the unity or disunity of power at the theistic ground. There are many different models that are applied at the terrestrial level. There we observe the occurrence of legal-political monism, dualism, trialism, etc., which results both from the creativity of the human race and confessional-civilizational conditions. The division of the unified model of power is realized in many variants, often reproducing the Locko-Monteskian dogma of the necessity of introducing institutional safeguards inside the system of power to prevent the absolutization of the system. Nevertheless, the radical implementation of this idea probably shall anihilate the statehood, which cannot exist without unquestionably centralized power.
Keywords: władza; podział; państwo; jedność